EXPLORING REFLECTIVE TEACHING PRACTICE IN PRIVATE PRIMARY SCHOOL IN RURAL AREA - Stevany Eryna Retnaningrum; Widya Caterine Perdhani; Serly Apryanty Jo (Jurnal Education and Development, 2022)
Reflective teaching is currently very important for every educator, especially during a pandemic like these days. By teaching reflective practice, teachers will be able to find out their shortcomings in learning so that they can develop professionalism in teaching. This study’s goal is to find out the level of understanding of teachers in private primary schools located in rural areas, what reflection activities they do, and the challenges they experience when doing reflective teaching. Purposive sampling was used to conduct the study which used a qualitative method. The data were collected through in-depth interview and questionnaire from eleven primary school teachers in a school in rural area. The study’s findings revealed that the teachers understand this reflective teaching only as a technique for evaluating their teaching effectiveness and tools to making improvements. Their reflection is divided into four types such as self-evaluation, student-evaluation, colleagues-evaluation, and professional development. Lack of time and to the point assignment were identified as the challenges in doing reflective teaching practice.